Medical thoracoscopy: Pahang experience - Ng, Teck Han; How, Soon Hin; Kuan, Yeh Chunn; H, Hasmah; Harun, Norra; Abdul Rani, Mohammed Fauzi (Malaysian Medical Associations, 2008)
Medical thoracoscopy has gain its popularity in Malaysia recently. This paper presents our early experience in thoracoscopy using semi-rigid fiberoptic thoracoscope. All thoracoscopy records since October 2006 were retrieved. The patients’ records, thoracocentesis investigations results, thoracoscopic findings and all pleural biopsy results were reviewed. Twenty-four thoracoscopic procedures on 22 patients in whom two patients had repeated thoracoscopy. Ten patients were confirmed carcinoma. Eight patients had inconclusive thoracoscopic pleural biopsy results. Three patients underwent pleurodesis for malignant effusion. One patient had adhesiolysis for empyema. There was no procedure-related deaths or intraoperative accidents. Thoracoscopy is a relatively safe procedure.